Effect of regular thicknesses on the microstructural and quantitative analysis for a hypo-eutectic ductile iron alloyed with Ni and V - Colin-García E.; Sánchez-Alvarado R.G.; Cruz-Ramírez A.; Suarez-Rosales M.A.; Portuguez-Pardo L.; Jiménez-Lugos J.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Ductile iron contains free graphite nodules within the metallic matrix, which generally consists of ferrite and pearlite in the as-cast condition. The casting thicknesses have a great influence on the size, shape, and quantity of the microconstituents of the metallic matrix and the graphite nodules and thus on the mechanical properties. In this study the cooling rate (caused by the casting thicknesses) on the metallic matrix and the nodular characteristics of a low alloyed ductile iron with 0.8 %Ni and 0.15 %V was investigated. The ductile iron was produced in a sandwich process with ladle inoculation. Six plates of different thicknesses, from 4.3 mm to 25.4 mm, were produced in a green sand mold. The microstructural characterization was performed by optical microscopy (OM), scanning electron microscopy (SEM), and the image J software using different quantification methods. The area method to determine the average nodule size and nodular structure provided more reliable results than the perimeter and total particle count methods. The hardness test on the Rockwell C scale was used for the mechanical characterization. The low content of vanadium added to the ductile cast iron had a negligible effect on the solidification pattern, which was mainly due to the graphitizing impact of the nickel and silicon addition. The results of the microstructural characteristics are therefore primarily due to the cooling rate, which is determined by the casting thickness. The thinnest casting section significantly improved the number of nodules (414 Nod/mm2), sphericity (0.96), and nodularity (96.21 %). In contrast, the thickest casting plate obtained the highest volume fraction of graphite (10.85 %) and the lowest volume fraction of unwanted particles (0.36 %). The high cooling rate in the thinnest casting plate resulted in the highest hardness of 31.56 HRC due to the higher volume fraction of the pearlite (33.7 %) and carbides (4.5 %).